A Bourdieusian Analysis of the Conversion Between Mathematical Achievement and Science Capital - Cooper, Grant (2023)
Mathematics serves as a universal language and set of thinking tools for science. While prior research indicates associations between academic success in mathematics and science, there is a gap in the research that explores the possible relationship between mathematical achievement during early secondary school (ages 11-13) and subsequent participation in advanced science courses during senior secondary school (beyond age 16). This research is valuable because it could provide further insights into how early achievement in non-science subjects is related to senior participation in science. The analysis of national mathematics test data found that students who studied different science subjects in senior secondary school all had stronger foundational mathematical skills than those who did not. The results differed according to science subjects. The analysis indicated differences of over 7.2 months of equivalent learning at early secondary level in favour of those who studied physics, 6.1 months for those who studied chemistry and 2.5 months for biology. I apply a Bourdieusian lens as a way of explaining students’ conversion of mathematical achievement into participation as a form of science capital. These findings add empirical weight to previous research promoting mathematics as a crucial foundation for science learning. This research has implications for policies and practices that promote learning in mathematics and science pathways.